Review and Support of the Relationship between Alliance Competence and Alliance Orientation - Gonzalo R. Llanos-Herrera (GECONTEC: Revista Internacional de Gestión del Conocimiento y la Tecnología, 2017)
This paper seeks to contribute to the understanding of the formation of strategic alliances among companies. Specifically, it seeks to understand the relationship between alliance competence (Lambe, Speakman & Hunt, 2002) and alliance orientation (Kandemir, Yaprak & Cavusgil, 2006), following some of the most important guidelines of the leading exponents of theories based on resources and dynamic capabilities.